Cystic fibrosis transmembrane regulator correction attenuates heart failure-induced lung inflammation - Uhl, Franziska E.; Vanherle, Lotte; Meissner, Anja (Frontiers in Immunology, 2022)
Heart failure (HF) affects 64 million people worldwide. Despite advancements in prevention and therapy, quality of life remains poor for many HF patients due to associated target organ damage. Pulmonary manifestations of HF are well-established. However, difficulties in the treatment of HF patients with chronic lung phenotypes remain as the underlying patho-mechanistic links are still incompletely understood. Here, we aim to investigate the cystic fibrosis transmembrane regulator (CFTR) involvement in lung inflammation during HF, a concept that may provide new mechanism-based therapies for HF patients with pulmonary complications. In a mouse model of HF, pharmacological CFTR corrector therapy (Lumacaftor (Lum)) was applied systemically or lung-specifically for 2 weeks, and the lungs were analyzed using histology, flow cytometry, western blotting, and qPCR. Experimental HF associated with an apparent lung phenotype characterized by vascular inflammation and remodeling, pronounced tissue inflammation as evidenced by infiltration of pro-inflammatory monocytes, and a reduction of pulmonary CFTR+ cells. Moreover, the elevation of a classically-activated phenotype of non-alveolar macrophages coincided with a cell-specific reduction of CFTR expression. Pharmacological correction of CFTR with Lum mitigated the HF-induced downregulation of pulmonary CFTR expression and increased the proportion of CFTR+ cells in the lung. Lum treatment diminished the HF-associated elevation of classically-activated non-alveolar macrophages, while promoting an alternatively-activated macrophage phenotype within the lungs. Collectively, our data suggest that downregulation of CFTR in the HF lung extends to non-alveolar macrophages with consequences for tissue inflammation and vascular structure. Pharmacological CFTR correction possesses the capacity to alleviate HF-associated lung inflammation.